c.1 - Nair, K.R.G.(ed.) (New Delhi, 1981)
The book brings together a number of interesting research papers on the burning issue of Regional Disparities in India, The authors include eminent experts in the field from the academic and other worlds as well as young researchers. The papers touch upon many important gene ral and specific aspects of the problem such as the need for Regional Planning, agriculture, industry, education, unemp loyment etc; some critically examine the role of Finance Commissions and of the Financial Institutions of the Central Government in tackling the problem of Regional Disparities in India; a few deal exclusively with the State of Kerala and highlight certain less known aspects of Kerala's development experience. The papers here have been chosen from those that were presented at a recent Confe rence in New Delhi Disparities in India" on Regional and the book con tains a brief report also rence proceedings.
Keywords: Regional economic